Calix[4]arene-based crab-like molecular sensors for highly selective detection of mercury and copper ions. Issue 1 (2nd January 2017) - Zadmard, Reza; Akbari-Moghaddam, Peyman; Darvishi, Shukufe
Abstract: In this work, two novel chemosensors based on calix[4]arene bearing (thio)barbituric acid groups (BC1 andBC2 ) were synthesised, and their structures were characterised by HRMS, NMR and FTIR. Furthermore, their binding properties towards various biologically relevant metal ions were studied by fluorescence titrations, 1 H NMR spectroscopies and Job's plot evaluations. The chemosensorBC1 displayed excellent binding affinity and selectivity towards Cu 2+, which was characterised using fluorescence spectroscopy. On the other hand, BC2 exhibited a very remarkable fluorescence enhancement as well as visible colour change from pale green to sunset yellow, in presence of Hg 2+ ions. Finally, Job's plot method revealed 1:1 binding stoichiometry for bothBC1 :Cu 2+ complex andBC2 :Hg 2+ complex. Abstract :